2015
DOI: 10.1002/ab.21603
|View full text |Cite
|
Sign up to set email alerts
|

Popularity differentially predicts reactive and proactive aggression in early adolescence

Abstract: Previous research has indicated that peer popularity is associated with aggressive behavior. However, it is not yet clear whether popularity is uniquely related to different functions of aggression. In this study, we examined associations between peer-perceived popularity, and reactive and proactive aggression using a cross-sectional and a longitudinal design. Yearly sociometric measures of popularity, and reactive and proactive aggression were gathered from 266 seventh and eight grade adolescents (Mage grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 44 publications
3
59
1
Order By: Relevance
“…In contrast, when studies control for levels of reactive aggression, proactive aggression is often uncorrelated with indicators of maladjustment or is positively associated with social competence, such as intelligence, popularity, and social skills (see Card & Little, 2006). A number of scholars have drawn on evolutionary and ethological frameworks to suggest that the effective use of aggression to successfully obtain resources, rewards, and power in social groups can be considered adaptive and socially competent (Hawley, 2014;Stoltz, Cillessen, van den Berg, & Gommans, 2016;Sutton et al, 1999).…”
Section: Functional Approaches To Aggressionmentioning
confidence: 99%
“…In contrast, when studies control for levels of reactive aggression, proactive aggression is often uncorrelated with indicators of maladjustment or is positively associated with social competence, such as intelligence, popularity, and social skills (see Card & Little, 2006). A number of scholars have drawn on evolutionary and ethological frameworks to suggest that the effective use of aggression to successfully obtain resources, rewards, and power in social groups can be considered adaptive and socially competent (Hawley, 2014;Stoltz, Cillessen, van den Berg, & Gommans, 2016;Sutton et al, 1999).…”
Section: Functional Approaches To Aggressionmentioning
confidence: 99%
“…Caputi et al (2012) indicated that theory of mind ultimately influenced peer relationships via social behavior. Children's prosocial tendencies are associated with their popularity (Deković and Gerris, 1994; Greener, 2000; Warden and Mackinnon, 2003), but specific antisocial behavior is related to adolescents' popularity (Cillessen and Borch, 2006; Mayeux, 2014; Stoltz et al, 2016). Thus, children tended to use theory of mind more prosocially, whereas adolescents tended to use it less prosocially in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The final XMQ scale was submitted to 1066 Dutch high school students as part of the Kandinsky Longitudinal Study (KLS) [37]. The KLS is a research project requested by the school in 2010 in order to help detect youth at risk for social and emotional problems in secondary education.…”
Section: Methodsmentioning
confidence: 99%